Ответ:
Объяснение:
№7:не уверен, но примерно 18
№8:
y = -⁷/₂x + 8
22 = -⁷/₂x + 8
22 - 8 = -⁷/₂x
14 = -⁷/₂x
-14 = ⁷/₂x
⁻¹⁴*²/₇ = x
-2 * 2 = x
x = -4
Ответ: -4
№9:
10 * (2 - x) + 11x = -3x
20 - 10x + 11x + 3x = 0
4x = -20
x = -5
Ответ: -5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
№7:
не уверен, но примерно 18
№8:
y = -⁷/₂x + 8
22 = -⁷/₂x + 8
22 - 8 = -⁷/₂x
14 = -⁷/₂x
-14 = ⁷/₂x
⁻¹⁴*²/₇ = x
-2 * 2 = x
x = -4
Ответ: -4
№9:
10 * (2 - x) + 11x = -3x
20 - 10x + 11x + 3x = 0
4x = -20
x = -5
Ответ: -5